Familial progressive supranuclear palsy. Issue 5 (May 1993) - Brown, J; Lantos, P; Stratton, M; Roques, P; Rossor, M
Abstract : A progressive extrapyramidal syndrome and dementia occurred in three members of one family. The age of onset was in the seventh decade and the affected individuals showed many of the clinical features of progressive supranuclear palsy (PSP). Necropsy of one individual revealed the neuropathological features of PSP. We propose that this family has a familial form of PSP and review the evidence in the literature that a familial form exists.